The Impact of Using Gamification in Learning Computer Science for Students in University - Oktaviati, Risna; Amril Jaharadak, Adam (International Journal of Engineering and Technology, 2018)
The utilization of technology can be implemented in education. Gamification is a new technology that used elements such as badges, level, and point of game play that implemented in a non-game context. In this research, the researcher analyzes some of the literature to establish in the extent of gamification to assist student’s motivation and engagement among Computer Science related subject. The researcher found that the most common element that implemented in learning Computer Science related subject were badges, point, level, and leaderboards. Implementing gamification elements in learning can be a tool that can motivate and engage the student in learning Computer Science.
Keywords: Gamification; Computer Science; Education; Badges; Point; Level; Leaderboards.